How Can Rice Farmers Gain Profit? An Analysis of Sharecropping Practice among Farmers, Landowners, and Laborers in Sukadiri Subdistrict of Tangerang - Haryanto, Lorenta In; Kurniaji, Aprilia Zirli (Jurnal Kawistara, 2023)
The production of rice as one of the main staple foods in Indonesia has been affected by changes in land-use that has led to a shift in land ownership. It is necessary to discuss whether the profit-sharing applied among farmers, landowners, and laborers provides benefits for farmers. This study aims to determine the characteristics, income, and efficiency of lowland rice farming with both a 50:50 crop sharing between farmers and landowners, and an 80:20 crop sharing between farmers and laborers. This study is based on survey and interviews on the sharecropping practice among rice farming community in the dry season (April – September) tahun 2022 in Sukadiri Subdistrict of Tangerang. Farming parameters are explained descriptively, and the farm efficiency is determined by the revenue-cost (R/C) ratio. A total sample of 44 farmers was determined purposively and proportionately. The findings demonstrated that rice farming gained a total income on the explicit cost of IDR7.311.519 per hectare. The R/C ratio of explicit cost for the sharecropping system is 4,76. Suppose the sharecropping system is replaced with a rent cash payment, the R/C ratio for total cost is 0,83 which results in a loss. This study concludes that the combination of 50:50 crop sharing with the landowner and 80:20 crop sharing with double-tapping laborers is beneficial for the existence of rice farming.